Effect of soaking time on the photoluminescence properties of cerium oxide nanoparticles - Deus, R. C.; Foschini, C. R.; Spitova, B.; Moura, F.; Longo, Elson [UNESP]; Simões, A. Z. (Elsevier, 2013)
The structural and photoluminescence properties at room temperature of CeO2 nanoparticles synthesized by a microwave-assisted hydrothermal method (MAH) under different soaking times on KOH mineralizer added to a cerium ammonium nitrate aqueous solution were undertaken. X-ray diffraction (XRD), Fourier transform infrared (FT-IR), Fourier transform Raman (FT-Raman) and photoluminescence (PL) measurements were employed. XRD revealed that the nanoparticles are free of secondary phases and crystallize in the cubic structure. The UV/vis absorption spectroscopy suggested the presence of intermediate energy levels in the band gap of structurally ordered powders. The most intense PL emission was obtained for nanoparticles which represent a lower particle size. © 2013 Elsevier Ltd and Techna Group S.r.l.
Keywords: A. Ceramics; B. Chemical syntheses; B. Powder metallurgy; C. X-ray diffraction